COVID-19, relationships, and contraception: Qualitative perspectives from emerging adults during the COVID-19 lockdown in Accra, Ghana - Adriana A.E. Biney; Esinam Kayi; D. Yaw Atiglo; Laud R. Sowah; Delali Badasu; Augustine Ankomah (Elsevier, 2023)
Globally, family planning services were disrupted during the height of the COVID-19 pandemic. Access to these services was a challenge for sexually active urban youth, and this warrants investigation. Using in-depth interview data, we qualitatively explored the effect of the lockdown on the relationship quality and contraception behaviour of emerging adults (19-24 year olds) who were in relationships during a specified lockdown period. Participants were purposively selected from a densely populated urban area in Accra and two public universities in that vicinity. In-depth interviews were also conducted with two family planning providers. Transcripts generated from the interviews were analysed thematically.Twelve of the 23 emerging adults were sexually active during the lockdown and varied in their reports on the stability of their relationships. The sexually inactive had disruptions in their relationships, mainly due to partner absence and a lack of sexual activity. Modern contraceptives, especially male condoms, were used but were obtained prior to the lockdown as confirmed by family planning providers. Traditional and folkloric methods were used by four participants. Participants reported no unintended pregnancies but rare cases of sexually transmitted infections.During the height of the COVID-19 pandemic, sexually active urban youth in Accra navigated the restrictions of lockdown imposition with diverse experiences. Therefore, understanding young adults' unique contraceptive behaviours and practices is essential to providing relevant sexual and reproductive health services to meet their needs. Discussions on the impacts of COVID-19 should be extended to sexual and reproductive health concerns such as access to contraceptives.